Designing Metacognitive Scaffolding Based on Science Talk to Enhance Students Scientific Argumentation - Rusdianto Rusdianto; Supeno Supeno; Ulin Nuha; Rizka Elan Fadilah; Soraya Firdausi; Ferry Budi Prasetya; Fauziyatul Iffah; Achmad Faisal Masruri; Li Yi Xuan (Universitas Negeri Semarang, 2026)
Scientific argumentation is essential for critical thinking and evidence-based reasoning in 21st-century science education. However, procedural teaching methods often neglect metacognitive regulation in argument construction. This study aims to analyze the validity, practicality, and effectiveness of student worksheets designed as operational representations of science talk-based metacognitive scaffolding. Employing a Research and Development (R&D) approach with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate), the research involved Grade 7E students at SMP Negeri 2 Panti, Jember. Data were gathered through expert validation, observation, pretest-posttest assessments, and student questionnaires. Results demonstrated high validity (95.5%) and practicality (95.5%). Effectiveness was evidenced by a moderate N-gain score of 0.67 and a 93.0% positive student response rate. These findings suggest that integrating metacognitive scaffolding and dialogic pedagogy significantly enhances students' scientific argumentation skills. This research contributes to the theoretical framework of argumentative learning design and metacognitive regulation in science education.